Pemberdayaan Masyarakat melalui Program Pelatihan dan Strategi Pengembangan Agribisnis Bonsai di Desa Ngunggahan Bandung Tulungagung - Sativa, Rima Dewi Oryza; Widiatmanta, Jeka; Nuraini, Risma (Universitas Islam Balitar, 2025)
Bonsai is a popular ornamental plant among the community. The use of wild plants as bonsai materials is something that needs to be developed to improve the community's economy. The purpose of thiscommunity service is to help bonsai farmers in Ngunggahan Village, so they are able to innovate in developingagribusiness by utilizing bonsai products from upstream to downstream as a source of high-quality livelihoods.The method used in the community service activities is a descriptive qualitative method through discussions,counseling, training, and direct evaluation of the community. Wild banyan and serut plants are widely foundin Ngunggahan Village, so they can be used as raw materials for bonsai nurseries that are inexpensive andhave high economic value. Bonsai making certainly requires expertise, but it does not rule out the possibilityof the general public to do it with guidance. Based on the Farming Business Analysis conducted, in a singleprocess of planting Banyan bonsai nurseries, profits of Rp. 1,971,200 and for bonsai serut Rp. 1,484,000 areobtained, this certainly makes the cultivation of wild bonsai plants a source of additional income for thecommunity. Bonsai product sales have been expanded using online media to reach a wider market. Utilizingfree internet access in Ngunggahan Village also facilitates online marketing.